Object Categorization Processing Differs According to Category Level: Comparing Visual Information Between the Basic and Superordinate Levels - Taniguchi, Kosuke; Kuraguchi, Kana; Takano, Yuji; Itakura, Shoji (Frontiers in Psychology, 2020)
Object category levels comprise a crucial concept in the field of object recognition. Specifically, categorization performance differs according to the category level of the target object. This study conducted experiments with two types of stimulus sequences (i.e., forward (presenting the target name before the line-drawing stimulus) and reverse (presenting the target name after the line-drawing stimulus) conditions) for both basic- and superordinate-level categorizations. Adult participants were assigned to each level and asked to judge whether briefly presented stimuluses included the same object and target name. Here, we investigated how the category level altered the categorization process. We also conducted path analyses and investigated whether the dimensions and shapes of the line-drawings (as related to object recognition) affected the categorization process between conditions. Results showed that the categorization process differed according to shape properties between conditions only for basic-level categorizations. For the forward condition, the bottom-up processing of primary visual information depended on matches with stored representations for the basic-level category. For the reverse conditions at the basic-level category, decisions depended on subjective ratings in terms of object-representation accessibility. Finally, superordinate-level decisions depended on higher levels of visual information in terms of complexity regardless of the condition. When recognizing an object, the given category level thus altered the processing of visual information in relation to shape properties. This indicates that decision processing is flexible in the context of object recognition depending on the criteria of the processed objects (e.g., category-levels).